Evaluating the user experience of a web-based child health record system / Nadia Abdul Wahab... [et al.] - Abdul Wahab, Nadia; Sahabudin, Nor Marlina; Osman, Aznoora; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2020)
The aim for this research is to design, develop and evaluate a web-based child health record system with appointment notification. This system has the ability to record all the medical information about a child such as the height, weight, treatments and medical conditions. It also has the ability to record the visits and immunization details, reminder for next visits and immunization appointments. A User Experience (UX) Test were conducted during the study to evaluate the system. User Experience Questionnaire (UEQ) is the instrument that is being utilized during the UX Testing to evaluate the user experience quality of a product. UEQ has been divided into six scales which are attractiveness, perspicuity, efficiency, dependability, stimulation and novelty. During the UX Testing, the users were given a chance to explore and evaluate the system. The result from the UX Testing indicates that most of the users agree that the system is attractive and has a good perspicuity, efficiency, dependability, stimulation and novelty. In conclusion, this research has achieved the objectives which are to design, develop and evaluate a Web-Based Child Health Record System with Appointment Notifications.